If it looks like a duck: final comment on early metallurgy and textile-production technologies in the southern Levant. (5th June 2017) - Ben-Yosef, Erez; Shamir, Orit; Levy, Janet
Abstract : We appreciate the emerging discussion on the identification of the recently discovered Chalcolithic artefacts from the Judean Desert, and the careful attention to detail by Langgut et al . (above) that helps to further clarify our current understanding of spinning and metallurgical technologies in this period. Yet while we agree that by its nature archaeology is full of surprises and exceptional discoveries, we argue, however, that especially in such cases as this, the supporting evidence should be robust. This is clearly not the situation here; regardless of Langgut et al .'s nuanced argumentation (above) on specific contextual observations, our interpretation of the lead artefact as a metallic macehead that happened to be found with its wooden shaft still attached (a rare find but paralleled in the hoard from the Cave of the Treasure) remains much simpler and more straightforward than the interpretation that this extremely rare metal was used as part of a mundane spinning implement (which has no parallels anywhere). As the limitation on space does not allow us to address each of the points raised by Langgut et al ., we leave it to the reader to assess the accuracy and relevance of their claims. In any case, their detailed response is only tangential to the essential line of our argument, which is related to weighing the available data and contextual information properly . The conclusion remains that while the observations that ostensibly connect the newly discovered artefacts to textile production are feeble and can be simply related to Ghassulian prestige metal objects (e.g. the use of wooden shafts and textiles in their carrying and maintenance), other observations make this connection difficult (as admitted also by Langgut et al . regarding the weight of the lead 'whorl'), if not impossible.